Telegram from Max Bredig to Marianne Homburger, March 19, 1941 - Bredig, Max Albert (1941)
Max Bredig (1902-1977) tells his sister, Marianne Homburger (1903-1986) that he completed an order, likely for a money transfer.
Keywords: Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968; Postal money orders; Bredig, Max Albert, 1902-1977